2019
DOI: 10.21037/gs.2019.10.03
|View full text |Cite
|
Sign up to set email alerts
|

A novel, adaptable, radiographically opaque, multi-plane continuous filament marker for optimizing tissue identification, radiation planning, and radiographic follow-up

Abstract: Background: In breast cancer treatment, marking the tumor bed is an important aspect of the surgical component of therapy. Clear delineation of the tumor bed allows radiation oncologists a defined target for planning and delivering postoperative radiation therapy (XRT). Tumor bed marking also allows radiographic follow-up of the tumor bed on subsequent breast imaging. The aim of this assessment is to evaluate the ease and feasibility of utilizing a tumor bed filament marker (VeraForm  , Videra Surgical inc., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…The filament was able to be placed easily at the time of lumpectomy taking an average of 4 minutes to place. 23 No adverse events related to FM placement were observed. The FM is not palpable for patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The filament was able to be placed easily at the time of lumpectomy taking an average of 4 minutes to place. 23 No adverse events related to FM placement were observed. The FM is not palpable for patients.…”
Section: Discussionmentioning
confidence: 93%
“…Initial experience with this marker was reported by Mitchell and colleagues. The filament was able to be placed easily at the time of lumpectomy taking an average of 4 minutes to place 23 . No adverse events related to FM placement were observed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, there may be alternative solutions. Recently, a new radiographic, 3D surgical filament marker was introduced to improve tumour bed marking for radiotherapy planning [299]. A similar study as that demonstrated in this thesis (one conducted by a multi-disciplinary team involving breast phantoms) can be conducted with different surgical markers to assess their reliability in improving tumour bed delineation accuracy.…”
Section: Further Applications Of the Realistic Breast Phantommentioning
confidence: 77%